(untitled) (The Educator Journal, 2025)
Objectives: This study assessed the level of knowledge and practice regarding menstrual hygiene among adolescent schoolgirls in Bhimsen Thapa Rural Municipality, Gorkha, Nepal, and examined key factors influencing these outcomes. Methods: A cross-sectional survey was conducted from May 25 to June 1, 2024, involving 448 adolescent girls. Data were gathered using a structured, self-administered questionnaire and analyzed using IBM SPSS version 25.0. Multivariate binary logistic regressionwas performed to identify significant predictors, with adjusted odds ratios (AORs) and 95% confidence intervals (CIs) reported. Results: The analysis revealed that 69% of respondents had good knowledge of menstrual hygiene, but only 28.6% exhibited proper hygiene practices. Alarmingly, just 1.6% disposed of used sanitary pads in appropriate dustbins. Girls aged 17–19 had significantly higher odds of possessing good knowledge [AOR = 7.78; 95% CI: 1.83–32.99], as did those from middle-income families [AOR = 0.51; 95% CI: 0.31–0.85]. Moreover, adolescentswhose mothers had attained secondary or higher education were more likely to practice better hygiene [AOR = 1.69; 95% CI: 1.04–2.77]. Conclusions: Despite a moderate level of awareness, hygienic practices among the girls were notably low. This gap highlights the need for targeted interventions to improve menstrual hygiene behaviors. Integrating menstrual health education into the school’s Breaking the Silence: Menstrual Hygiene Knowledge and Practices Among Adolescent Girls in Rural Gorkha, Nepal 28 integrated curriculum and conducting parent-focused sessions could foster community-level understanding and support. Promoting awareness and empowering adolescent girls through education and parental involvement are essential to enhancing menstrual hygiene management in rural Nepal.